SEKOLAH RUMAH SEBAGAI SALAH SATU BENTUK PENDIDIKAN INFORMAL: LEGALITAS DAN RAGAM PENDEKATAN PEMBELAJARANNYA - Mohammad Siddiq; Hartini Salama (usat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2021)
The reality of homeschooling as a choice for parents in providing education to children is one of the efforts to solve various educational problems that exist in society. However, the legality of home education and the learning approach has become a significant issue. With a descriptive qualitative approach, this research reveals the legal aspects and the various learning approaches of home education. Regarding the legality of homeschooling, the government should carry out the mandate of the Constitution, ensuring that every citizen receives a proper education, as stated in Article 31 of the 1945 Constitution, which is further elaborated in Law Number 20 of 2003 concerning the National Education System, Government Regulation Number 57 of 2021 concerning National Education Standards, and Regulation of the Minister of Education and Culture Number 129 of 2014 concerning Home Schools. Homeschooling is one of the informal education paths which is carried out by families. The approach in the practice has a wide range, from very unstructured models such as unschooling to highly structured ones such as school at home. To facilitate home school practitioners, the existence of a test center will significantly encourage the emergence of initiative and creativity in the development of learning methods and education models.